Kefahaman Ibadat Solat Fardu dalam Kalangan Pelajar Muslim: Kajian Tinjauan di Kolej Komuniti Bukit Beruang, Melaka (Sains Humanika, 2015)
The research aim to find out the in-depth knowledge among the muslim students of Kolej Komuniti Bukit Beruang, Melaka on the topic of performing the sholah. This researcher has used questionaire as main research instrument. One set of the questionaire contains 20 items distributed to the respondents. Data gained from the respondents was analyzed using the Statistical Package For Social Sciences (SPSS) version 2.00 for further statistical analysis. This research focus on three aspects that divided mainly into; the general understanding of performing the sholah by the students, two, the respondents perception on order by Allah to perform the sholah and third, the retribution for those who did not perform the sholah. 75 muslim respondents were selected that consist of final year students of the college. They were randomly selected by the researcher from five different programmes offered i.e: Certificate in Electrical, Certificate in Light Vechicle Services, Certificate in Cullinary, Hotel Managment and Operation and Certificate in Fashion. The analysis showed the general understanding and conception of performing the sholah among respondents is high. Respondents also showed high understanding and knowledge to two other research parameters that punishment to those who did not perform the sholah and congregation in sholah. As conclusion, this researcher hopes that the lecturers will continue playing the role and commitment in ensuring, motivitating and by guiding students to uphold the duty as a muslim programmes that focus on Islamic teaching and responsibility such as seminars, conferences etc will ensure maximum comprehension and execution of the sholah in their daily lives.
Keywords: Understanding of sholah; sholah; fardu sholah; Community College Bukit Beruang; Melaka